Effect of lipid viscosity and high-pressure homogenization on the physical stability of "Vitamin E" enriched emulsion. (August 2015) - Alayoubi, Alaadin; Abu-Fayyad, Ahmed; Rawas-Qalaji, Mutasem M.; Sylvester, Paul W.; Nazzal, Sami
Abstract Recently there has been a growing interest in vitamin E for its potential use in cancer therapy. The objective of this work was therefore to formulate a physically stable parenteral lipid emulsion to deliver higher doses of vitamin E than commonly used in commercial products. Specifically, the objectives were to study the effects of homogenization pressure, number of homogenizing cycles, viscosity of the oil phase, and oil content on the physical stability of emulsions fortified with high doses of vitamin E (up to 20% by weight). This was done by the use of a 27-run, 4-factor, 3-level Box–Behnken statistical design. Viscosity, homogenization pressure, and number of cycles were found to have a significant effect on particle size, which ranged from 213 to 633 nm, and on the percentage of vitamin E remaining emulsified after storage, which ranged from 17 to 100%. Increasing oil content from 10 to 20% had insignificant effect on the responses. Based on the results it was concluded that stable vitamin E rich emulsions could be prepared by repeated homogenization at higher pressures and by lowering the viscosity of the oil phase, which could be adjusted by blending the viscous vitamin E with medium-chain triglycerides (MCT).